Temperature, trophic state, and carrying capacity govern pelagic size spectra in the Atlantic Ocean - Ralf Schwamborn; Tim Dudeck; Claire Carré; Gabriel Bittencourt Farias; María Couret; Javier Díaz-Pérez; Mathilde Dugenne; Gabriela Guerra Araújo Abrantes de Figueiredo; Thierry Frédou; Flávia Lucena-Frédou; Xiomara F.G. Díaz; Dawit Yemane; et al. (Progress in Oceanography, 2026)

Seasonal Changes of Size Spectra of the Benguela Offshore Mesopelagic Ecosystem Compartment in Relation to Primary Production - Heino O. Fock; Henrike Andresen; Javier Díaz Pérez; Tim Dudeck; Gabriela Figueiredo; Thierry Frédou; Dawit Y. Ghebrehiwet; Cristina González‐García; José M. Landeira; Simone Lira; Emilio Marañón; Leandro Nole Eduardo; et al. (Marine Ecology, 2025)
Seasonal differences in marine size spectra of micronekton at the shelf‐ocean interface of the northern (NBUS) and southern Benguela upwelling system (SBUS) in Feb–Mar 2019 and Sep–Oct 2021 were analysed for mesopelagic fishes and total micronekton, the latter also including invertebrates. A resource dependent population model based on the metabolic theory of ecology (MTE) containing resource and temperature terms and a term representing a transfer function was applied to test three different types of size spectra slope estimates. The model fitted best with linear slopes calculated of log‐binned averaged community biomass (LBNbiom method), while maximum likelihood and quantile regression estimates proved less effective. The best model for total micronekton contained significant effects both for resource term and transfer function, but not for temperature, and was 3.6 times more effective explaining the data than a non‐MTE model. Normalized biomass size spectra (NBSS) slopes of the total micronekton were in the theoretical range between −0.80 and −1.37, where the near‐equilibrium slope of −0.80 was obtained for the SBUS under oligotrophic conditions in 2021. Seasonally, NBSS slopes were steeper in the NBUS than in the SBUS. The slopes for the fishes' subcomponents ranged from −0.23 to −0.92, where values > −0.75 fall outside the theoretical range, suggesting that selecting taxonomic subsets for size spectrum analysis is problematic. The importance of the productivity regime shaping the biomass spectrum directly through the resource level and indirectly through the transfer function is highlighted. For mesopelagic fishes, generation time and fecundity are applied to explain slopes > −0.75.

Trophic ecology of squids in the Benguela Upwelling System elucidated by combining stomach content, stable isotope and fatty acid analyses - Kira Izabela Kremer; Wilhelm Hagen; Daniel Oesterwind; Sabrina Duncan; Maya Bode-Dalby; Sabrina Dorschner; Tim Dudeck; Anne F. Sell (Marine Biology, 2025)
Squids occur worldwide in marine ecosystems and play a major role in pelagic food webs by connecting lower and higher trophic levels. Their high feeding intensities and pronounced diel vertical migrations make squids important components of nutrient cycles in marine ecosystems. This study assessed the trophic position and nutritional ecology of a squid species assemblage in the Benguela Upwelling System (BUS) by combining stomach content, stable isotope and fatty acid trophic marker analyses. Samples were collected in the northern (nBUS) and southern (sBUS) BUS in austral spring 2021. A total of 20 squid species from eleven families were identified. Stomach content analyses showed that squid species preyed on a variety of organisms ranging from crustaceans to lanternfishes (Myctophidae) and flying squids (Ommastrephidae). Stable isotope analyses revealed significant differences in δ 15 N values of small squids (dorsal mantle length < 10 cm) between the two subsystems, but none in those of large squids (dorsal mantle length > 10 cm). Trophic levels ranged from 2.2 to 5.0. Isotopic niche width was widest in the families Ommastrephidae and Cranchiidae. Principal component analyses of fatty acid compositions displayed distinct clusters separating squid families and different prey taxa. This study shows that nBUS and sBUS squids exploit a large variety of pelagic prey organisms and that trophic differences are primarily dependent on squid species and size. The results emphasize the squids’ importance as interlinking element in pelagic food webs and their key function in energy transfer between epi- and mesopelagic layers.

Variability of prey preferences and uptake of anthropogenic particles by juvenile white seabream in a coastal lagoon nursery ground - Carolin Müller; Karim Erzini; Tim Dudeck; Joana Cruz; Luana Santos Corona; Felipe Eloy Abrunhosa; Carlos Manuel Lourenço Afonso; Miguel Ângelo Franco Mateus; Cristina Orro; Pedro Monteiro; Werner Ekau (Environmental Biology of Fishes, 2023)
Marine plastic litter, originating from land-based sources, enters the marine environment by passing through coastal ecosystems such as lagoons and estuaries. As early life history stages (ELHS) of many commercially important fish species rely on these transitional areas as nursery grounds, we hypothesized that they encounter a spatial gradient of habitat quality and pollution from inner to outer parts of their vital environment. With sizes < 5 mm, anthropogenic particles (AP), among them microplastic (MP) fibers and fragments, entail a high bioavailability for ELHS of fish, potentially facilitating AP uptake at early developmental stages which may have implications for their survival and growth. This study provides a contextualization baseline between feeding preferences and uptake of AP by the white seabream Diplodus sargus (Linnaeus, 1758) in an estuarine nursery ground on the southern coast of Portugal. Juvenile fish showed a generalized, omnivorous feeding mode with differences in trophic resource utilization between individuals collected at distinct seagrass meadows in the lagoon. A total of 23.13% of the fish ( n = 147) were detected with AP in the gastrointestinal tract, and the mean number of AP per AP-feeding individual was 1.64 ± 1.04, with anthropogenic fibers ( n = 47) occurring more frequently than fragments ( n = 9). Knowledge of the underlying factors for MP ingestion will be greatly enhanced by considering environmental conditions along with species-stage and life-stage specific feeding modes and prey preferences which shape the uptake probability of anthropogenic fibers and fragments.